Ryanodine Receptors in Autophagy: Implications for Neurodegenerative Diseases? - Vervliet, Tim (Frontiers in Cellular Neuroscience, 2018)
Intracellular Ca2+ signaling is important in the regulation of several cellular processes including autophagy. The endoplasmic reticulum (ER) is the main and largest intracellular Ca2+ store. At the ER two protein families of Ca2+ release channels, inositol 1,4,5-trisphosphate receptors (IP3R) and ryanodine receptors (RyR), are expressed. Several studies have reported roles in the regulation of autophagy for the ubiquitously expressed IP3R. For instance, these channels suppress basal autophagic flux by promoting mitochondrial metabolism, while they also promote the rapid initial increase in autophagic flux in response to nutrient starvation. Insights into the contribution of RyRs in autophagy have been lagging significantly compared to the advances made for IP3Rs. This is rather surprising considering that RyRs are predominantly expressed in long-lived cells with specialized metabolic needs, such as neurons and muscle cells, in which autophagy plays important roles. In this review, recent studies revealing roles for RyRs in the regulation of autophagy will be discussed. Several RyR-interacting proteins that have been established to modulate both RyR function and autophagy will also be highlighted. Finally, the involvement of RyRs in neurodegenerative diseases will be addressed. Inhibition of these channels has not only been shown to be beneficial for treating several of these diseases but also regulates autophagy.